E-MARKETING: BUSINESS in DEVELOPING SMEs IN INDONESIA - WINARSO, WIDI (International Journal of Psychosocial Rehabilitation, 2020)
SMEs is one of the sectors that provides great benefits for both the region and the community, with its ability to absorb a large workforce, this sector responds to the imbalance between the growth of the productive age population and the availability of jobs, besides SMEs also have a positive contribution in increasing the GDP of a region. The problem that is often found in the development of the SMEs sector is the marketing problem. The development of the internet age is increasingly widely known by the people of Indonesia in particular. E-Marketing is any business that is carried out to market a product or service using the Internet media. In its development the internet has become one of the most effective media in promoting a product that can ultimately support the sale of a product. With descriptive methods and using secondary data obtained from relevant agencies, this study is expected to provide an illustration that e-marketing is an alternative marketing with market opportunities that are still very broad.